2008
DOI: 10.1002/chem.200802048
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Ambient‐Temperature Copper‐Catalyzed Atom‐Transfer Radical Addition (ATRA) in the Presence of Free‐Radical Initiator (V‐70) as a Reducing Agent

Abstract: Copper can do it! Highly efficient ambient‐temperature copper‐catalyzed ATRA of polyhalogenated compounds to alkenes in the presence of free‐radical initiator 2,2′‐azobis(4‐methoxy‐2,4‐dimethyl valeronitrile) (V‐70) is reported. V‐70 has been shown to be a very effective reducing agent, enabling selective formation of the ATRA product with α‐olefins and highly active monomers, such as methyl acrylate, methyl methacrylate, and vinyl acetate, by using as little as 0.002 mol % of copper (see figure).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(31 citation statements)
references
References 26 publications
(35 reference statements)
1
30
0
Order By: Relevance
“…The reactions can also be run in a normal flask in sunlight with equally good results (Table 1, entry 2), whereas no conversion is observed when the reactions are run in the dark (Table 1, entry 5). The copper‐catalyzed ATRA reaction between alkenes and CBr 4 at room temperature, employing remarkably low concentrations (down to 0.002 mol %) of [Cu II (tpma)X][X] (tpma=tris(2‐pyridylmethyl)amine, X=Cl, Br), has been achieved previously, however, 5 mol % of the radical initiator 2,2′‐azobis(4‐methoxy‐2,4‐dimethyl valeronitrile) (V‐70) must be employed as an additive 11…”
Section: Methodsmentioning
confidence: 99%
“…The reactions can also be run in a normal flask in sunlight with equally good results (Table 1, entry 2), whereas no conversion is observed when the reactions are run in the dark (Table 1, entry 5). The copper‐catalyzed ATRA reaction between alkenes and CBr 4 at room temperature, employing remarkably low concentrations (down to 0.002 mol %) of [Cu II (tpma)X][X] (tpma=tris(2‐pyridylmethyl)amine, X=Cl, Br), has been achieved previously, however, 5 mol % of the radical initiator 2,2′‐azobis(4‐methoxy‐2,4‐dimethyl valeronitrile) (V‐70) must be employed as an additive 11…”
Section: Methodsmentioning
confidence: 99%
“…However, the use of the roomtemperature radical initiator 2,2-azobis(4-methoxy-2,4-dimethyl valeronitrile), known as V-70, as the reducing agent, provided efficient ATRA reactions with -olefins with only 0.005 mol % of catalyst loading. [21] The main disadvantage of this strategy is that AIBN or V-70 also promote the generation of free radicals, which function as efficient chain-transfer agents, in the case of the more reactive monomers such as styrene, methyl acrylate, or methyl methacrylate. Recently, they have demonstrated the efficacy and versatility of ascorbic acid as a reducing agent (Scheme 7) in copper-catalyzed ATRA reactions: [22] the addition of 7-20 mol% of ascorbic acid relative to alkene, the selective formation of the monoadduct with a catalyst loading of as as low as 5 x 10 -3 mol% was observed.…”
Section: Copper-based Catalystmentioning
confidence: 99%
“…Both processes originated from well-known Kharasch addition in which polyhalogenated compounds were added to alkenes via free-radical means (13,39,40). Recent studies have also indicated that TPMA is a superior complexing ligand in ATRA (13,33,40,(44)(45)(46)(47)(48)(49)(50)(51)(52)(53)(54) and ATRP (49,(55)(56)(57)(58) that utilize reducing agents. The role of a reducing agent in both systems is to continuously regenerate the activator species (copper(I) complex) from the corresponding deactivator (copper(II) complex).…”
Section: Catalysis With Transition Metal Complexes Containing Tpma LImentioning
confidence: 97%